CASE BASED REASONING UNTUK MENDIAGNOSA PENYAKIT ANAK MENGGUNAKAN METODE BLOCK CITY - Marnon C. Y Mage; Derwin R Sina; Tiwuk Widiastuti (Universitas Nusa Cendana, 2017)
The Case Based Reasoning (CBR) method is one of the methods to build a system that works by diagnosing new cases based on old cases that have occurred and providing solutions to new cases based on old cases with the highest similarity values. In this study, the authors apply CBR to diagnose diseases of children aged 1-12 years. Sources of system knowledge were obtained by collecting patient medical record files in 2014 and 2015. The calculation of similarity values using the Block City Gower method with a fairness value is 70%. This system can diagnose 10 illnesses based on 48 existing symptoms. The output of the system in the form of the illness experienced by the patient based on symptoms implanted by non-physician medical personnel, handling solution and presentation similarities with the previous case to show the truth level of the diagnosis. Based on the test of 83 new cases obtained system accuracy of 75,90%.